Volatile Anaesthetic Depression of the Carotid Body Chemoreflex-Mediated Ventilatory Response to Hypoxia: Directions for Future Research. (6th April 2014) - Pandit, J. J.
Abstract : In assessing whether volatile anaesthetics directly depress the carotid body response to hypoxia it is necessary to combine in meta-analysis studies of when it is "functionally isolated" (e.g., recordings are made from its afferent nerve). Key articles were retrieved (full papers in English) and subjected to quantitative analysis to yield an aggregate estimate of effect. Results from articles that did not use such methodology were assessed separately from this quantitative approach, to see what could be learned also from a nonquantitative overview. Just 7 articles met the inclusion criteria for hypoxia and just 6 articles for hypercapnia. Within these articles, the anaesthetic (mean dose 0.75, standard deviation (SD) 0.40 minimum alveolar concentration, MAC) statistically significantly depressed carotid body hypoxic response by 24% (P = 0.041 ), but a similar dose (mean 0.81 (0.42) MAC) did not affect the hypercapnic response. The articles not included in the quantitative analysis (31 articles), assessed qualitatively, also indicated that anaesthetics depress carotid body function. This conclusion helps direct future research on the anaesthetic effects on putative cellular/molecular processes that underlie the transduction of hypoxia in the carotid body.